City information modeling como ferramenta na gestão urbana: aplicação da integração GIS-BIM - Melo, Francisca Ires Vieira de (2022)
Urban centers have become increasingly complex environments, causing changes that are expressed both in the city landscape and in people's behavior and lifestyle, causing, thus, transformations that directly impact the urban socio-spatial structuring. In this way, this study aims to elaborate guidelines for GIS-BIM integration, addressing a script related to parameters interconnected to decision making in urban planning, so that it serves, through the CIM, as an instrument that allows the facilitation of decision making in city planning and management. For this, the method of Design Science Research (DSR) will be employed, through which an artifact presenting approaches of GIS-BIM integration was elaborated, through the compatibility of georeferencing and modeling of the São Judas Tadeu neighborhood of the city of Pau dos Ferros/RN - Brazil. As results, a proposal was developed with guidelines for GIS-BIM integration, which were validated by applying the modeling of the neighborhood with 1.496 modeled buildings, where the parameters of gauge, built area and projection area of the building can be extracted automatically. Thus, the development of this integration contributes to reducing the cost of time and resources to produce geographic information, in addition to facilitating the visualization and understanding of the studied territory.